POTRZEBNE NA JUTRO !!!!!
PROSZĘ O SZYBKĄ ODPOWIEDŹ :)

rozwiąrz układ równań metodą podstawiania:)

a)
y\3 - x\4 + ⅓ = ½
y\4 - 5\8 = - x\3 - ½

b)
2x - 3( x + y) + 14 = y - 2
2( x - y) + 3y + 3 = 2y - 1

c)
x - y\2 - 1 = - 1\6 - ( x - 2 y)\3
x\3 - y\2 =5\6

d)
4( 2a - b)\ 3 + b\2 =½(a - b) + 8 + 2(a + b)\3
-1 + (3 - b)\4 = (a + 1)\3

e)
a(a - b) + 2(b - 2)(a + 3) = ( a + b) ( a - 1)
a\3 - b\2 = 1\3

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-23T18:21:12+01:00
A)
y\3 - x\4 + ⅓ = ½ /*12
y\4 - 5\8 = - x\3 - ½ /*24

4y-3x+4=6
6y-15=-8x-12

4y-3x=6-4
6y+8x=-12+15

4y-3x=2
6y+8x=3

4y=2+3x
6y+8x=3

y= ½+¾x
6(½+¾x)+8x=3

y= ½+¾x
3+4,5x+8x=3

y= ½+¾x
12,5x=0

y= ½+¾x
x=0

y=½
x=0
----------------------
b)
2x - 3( x + y) + 14 = y - 2
2( x - y) + 3y + 3 = 2y - 1

2x-3x-3y+14=y-2
2x-2y+3y+3=2y-1

-x-4y=-16
2x-y=-4

-x=4y-16 /*(-1)
2x-y=-4

x=16-4y
2(16-4y)-y=-4

x=16-4y
32-8y-y=-4

x=16-4y
-9y=-4-32

x=16-4y
-9y=-36 /*(-1)

x=16-4y
9y=36

x=16-4y
y=4

x=0
y=4
-----------------------------
c)
x - y\2 - 1 = - 1\6 - ( x - 2 y)\3 /*6
x\3 - y\2 =5\6 /*6

6x-3y-6=-1-2( x - 2 y)
2x-3y=5

6x-3y-6=-1-2x +4y
2x-3y=5

8x-7y=5
2x-3y=5

8x-7y=5
2x=5+3y

8x-7y=5
x=2,5+1,5y

8(2,5+1,5y)-7y=5
x=2,5+1,5y

20+12y-7y=5
x=2,5+1,5y

5y=5-20
x=2,5+1,5y

5y=-15
x=2,5+1,5y

y=-3
x=2,5+1,5*(-3)

y=-3
x=-2
-----------------------
d)
4( 2a - b)\ 3 + b\2 =½(a - b) + 8 + 2(a + b)\3 /*6
-1 + (3 - b)\4 = (a + 1)\3 /*12

8( 2a - b)+3b=3(a - b)+48+4(a + b)
-12+3(3-b)=4(a+1)

16a-8b+3b=3a-3b+48+4a+4b
-12+9-3b=4a+4

16a-8b+3b-3a+3b-4a-4b=48
-3b-4a=4+12-9

9a-6b=48
-3b-4a=7

-6b=48-9a /*(-1)
-3b-4a=7

6b=9a-48
-3b-4a=7

b=1,5a-8
-3(1,5a-8)-4a=7

b=1,5a-8
-4,5a+24-4a=7

b=1,5a-8
-8,5a=7-24

b=1,5a-8
-8,5a=17 /*(-1)

b=1,5a-8
8,5a=-17

b=1,5a-8
a=-2

b=1,5*(-2)-8
a=-2

b=-11
a=-2

------------------------
e)
a(a - b) + 2(b - 2)(a + 3) = ( a + b) ( a - 1)
a\3 - b\2 = 1\3 /*6

a²-ab+2(ab+3b-2a-6)=a²-a+ab-b
2a-3b=2

a²-ab+2ab+6b-4a-12=a²-a+ab-b
2a-3b=2

a²-ab+2ab+6b-4a-a²+a-ab+b=12
2a-3b=2

7b-3a=12
2a=2+3b

7b-3a=12
a=1+3/2b

7b-3(1+3/2b)=12
a=1+3/2b

7b-3-4,5b=12
a=1+3/2b

2,5b=15
a=1+3/2b

b=6
a=1+3/2*6

b=6
a=10

1 5 1